PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL PADA 19 KABUPATEN DAN KOTA DI SUMATERA BARAT - Devi Oktavia; Joni Fernandes (LP2M Universitas Bina Bangsa, 2021)
Low budget absorption in Capital Expenditure can have an impact, including the poor regional infrastructure owned now also the absence of significant additional number of projects in the field of new infrastructure, the absence of basic infrastructure such as ports, roads, clean water processors, and power plants. The purpose of this study was to find out how much influence the original income of the region and general allocation funds on capital expenditure in 19 districts and cities in west Sumatra in the period 2015-2019. Sampling technique uses the total sampling method and obtained as much as 95 data. Data obtained from the Central Statistics Agency of West Sumatra Province through the www.sumbar.bps.go.id website. The analysis method used is regression analysis of panel data with the help of the E-Views 8 application. After the Hausman-Test, it was decided to choose to use the Fixed Effect Model method. The results showed that PAD and DAU have a positive effect on capital expenditure, both respectively and together